ANALISIS KONSEPSI PESERTA DIDIK DALAM MENYELESAIKAN SOAL GERAK MELINGKAR BERATURAN MENGGUNAKAN TES DIAGNOSTIK - Apriyani, Dwi; Sirait, Judyanto; Hidayatullah, Muhammad Musa Syarif (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to describe the profile of students' conceptions of uniform circular motion (GMB) through a four-tier diagnostic test. This study uses a qualitative method in the form of survey research involving 27 students of class X MIPA SMA Negeri 1 Rasau Jaya for the academic year 2021/2022. This research is a qualitative descriptive study. The data collection in this study used the instrument of conceptual test questions arranged in the form of a four-tier diagnostic test presented on google form and interviews with students directly. The four-tier diagnostic test given to students consists of four levels, namely the main multiple choice questions, the level of confidence in the answers, the reasons given, and the level of confidence in the reasons. Based on the results of the analysis obtained 15.74% of students who understand the concept of uniform circular motion (GMB), 39.81% of students who do not understand the concept, 40.74% of misconceptions and 3.7% of students are categorized as errors. As for this research, it can be concluded that the four-tier diagnostic test can identify the conceptions possessed by students, in this study also states that in the uniform circular motion (GMB) material, students experience more misconceptions.